DETECTION AND CORRECTION SYSTEM FOR PUNCTUATION ERRORS IN INDONESIAN SPELLING ACCORDING TO THE ENHANCED SPELLING (EYD) - Julyawan Abadi, Muhamad
Punctuation plays a pivotal role within the spelling system, aiding readers in achieving a clearer comprehension of the author's intent. Frequent errors in the utilization of punctuation marks are a prevalent issue in Indonesian writing, stemming from a multitude of factors, including a lack of familiarity with the rules governing their use and individual writing habits. To address this challenge, our research employs the Design Research Methodology (DRM) to construct a punctuation detection and correction system. The system is developed through fine tuning the dataset using the pre trained XLM-RoBERTa model. Evaluation of the system yields promising results, with F1-score values of 82.49% during system validation and 76% during expert validation. Notably, the system demonstrates heightened sensitivity in identifying punctuation marks such as periods, commas, and question marks. Consequently, this system represents an effective alternative educational tool for enhancing comprehension of punctuation mark usage within Indonesian spelling.